THE USAGE OF ANIMAL IMAGERY IN THE WORKS OF TED HUGHES - Isamova Dilfuza Rakhmatovna; Haydarov Anvar Askarovich (Modern American Journals, 2025)
The article examines the imagery of animals in poetry in the works of the modern British poet Ted Hughes, explains what factors determined by nature and animals.
Keywords: Modern poetry of Great Britain, the work of Ted Hughes, imagery poetry, poetry about animals.